Faktor-Faktor yang Berhubungan dengan Tingkat Kecemasan Pasien Pre Operasi Appendiktomi Diruang Kamar Bedah RSU Bhakti Asih - Alpin Edo Andopa; Dessi Juwita; Rizki Hallifah Ashri; Any Kurniawati (Jurnal Rumpun Ilmu Kesehatan, 2024)
Diabetes Mellitus Type 2 is a metabolic disorder characterized by increased blood sugar levels (hyperglycemia). Diabetes can affect the quality of life with several aspects, namely diabetes care, symptoms of diabetes, and chronic complications that cause high morbidity and mortality.. Objectives: This is to find outDeterminant Factors of Quality of Life of Type 2 Diabetes Mellitus Patients at Bhakti Asih Hospital Tangerang in 2024. The research method is quantitative research with a Cross Sectional approach. Methods: sample was 55 patients using a purposive sampling technique. The knowledge level instrument usedDKQ-24 questionnaire (Diabetes Knowledge Questionnaire), Diet pattern questionnaire using FFQ, Activity pattern questionnaire using GPAQ (global physical activity questionnaire), Medication adherence questionnaire using Medication Adherence Report Scale (MARS),measurement of quality of life using the Diabetes Quality Of Life (DQOL) questionnaire. Data were analyzed using the Statistical Test used was the bivariate test, namely Chi-Square and the multivariate test, namely the Backward logistic regression method. Results: shows that the Physical Activity variable has the largest coefficient B value and OR value, which means that among the four variables, the Physical Activity variable is the most dominant factor related to the Quality of Life of Type 2 Diabetes Mellitus Patients. Based on the results of the model analysis, the Negelkelke R Square value is 49.9%, meaning that the variables of Knowledge Level, Diet, Physical Activity, and Blood Sugar Level Examination on the Quality of Life of Type 2 Diabetes Mellitus Patients are 49.9% and the rest can be explained by other variables outside this study.Conclusion,In this study, the level of knowledge, diet, physical activity, and blood sugar level examinations were related to the quality of life of type 2 diabetes mellitus patients.